Mycobacterium genavense in the Netherlands: an opportunistic pathogen in HIV and non-HIV immunocompromised patients. An observational study in 14 cases - Hoefsloot, W.; van Ingen, J.; Peters, E.J.G.; Magis-Escurra, C.; Dekhuijzen, P.N.R.; Boeree, M.J.; van Soolingen, D. (Clinical microbiology and infection, 2013)
Mycobacterium genavense is an opportunistic non-tuberculous mycobacterium previously mostly associated with HIV-infected patients with CD4 counts below 100/µL. In this retrospective observational study of medical charts we studied all Dutch patients in whom M. genavense was detected between January 2002 and January 2010. Of the 14 patients identified, 13 (93%) showed clinically relevant M. genavense disease. All patients with M. genavense disease were severely immunocompromised, including HIV-infected patients, solid organ transplant recipients, those with chronic steroid use in combination with other immune modulating drugs, recipients of chemotherapy for non-Hodgkin lymphoma, and those with immunodeficiency syndromes. Two patients had non-disseminated pulmonary M. genavense disease. Of the 12 patients treated, eight (75%) showed a favourable outcome. Four patients died in this study, three despite treatment for M. genavense disease. We conclude that M. genavense is a clinically relevant pathogen in severely immunocompromised patients that causes predominantly disseminated disease with serious morbidity and mortality. M. genavense is increasingly seen among non-HIV immunocompromised patients.